Pembentukan Fasa Co3O4 Dengan Metoda Dekomposisi CoCO3 Menggunakan Sinar Diffraksi - Lusiana Lusiana; Sigit Dwi Yudanto (Politeknik Negeri Padang, 2019)
Experiments have been carried out to obtain the decomposition of cobalt carbonate cobalt oxide to be used as raw material for the manufacture of calcium cobalt oxide thermoelectric materials. The experiments were performed by heating cobalt carbonate powder material (CoCO3) from Kanto Chemical with a temperature of 1000°C. Heating aims to obtain Co3O4 phase. Co3O4 phase is what will be used in the manufacture of thermoelectric materials based on the phase diagram of the system Ca-Co-O. The results of X-ray diffraction CoCO3 materials are heated to 1000°C showed that Co3O4 phase has been formed. Analysis quantitative diffraction pattern shows the diffraction peaks are the property throughout the Co3O4 phase. The crystal structure of Co3O4 is Face Centered Cubic (FCC) with space group F d -3 m. Lattice parameters of the diffraction pattern is the result of smoothing a = 8.0838 Å.